(untitled) (Journal of Interdisciplinary Insights, 2024)
This study, grounded in the PREAM model (Protective Factors, Risk Factors, Exposure, Awareness, and Motivation) and integrating theories from Positive Psychology, explores the current state and psychological characteristics of college students participating in volunteer services. Through questionnaire surveys and semi-structured interviews, the study analyzes the motivations, psychological needs, and the impact of volunteer service on the mental health and well-being of college students. The results reveal that volunteer service not only helps enhance college students’ psychological resilience but also significantly improves their subjective well-being. Based on these findings, the study proposes corresponding policy recommendations to further promote volunteer activities among college students.